REAKSI INVESTOR TERHADAP PEMILIHAN AUDITOR SPESIALIS INDUSTRI PADA PERUSAHAAN KELUARGA DI BURSA EFEK INDONESIA - Eko Suyono (University of Merdeka Malang, 2015)
This study aimed to investigate the link between family firm and specialist auditor selection, the investorreaction in family and non family firms on specialist auditor selection, the influence of family CEO and hiredCEO on specialist auditor selection, and the influence of divergence between cash flow right and control righton auditor specialist selection.This research applied purposive sampling method by using 108 companies thatwere selected from 534 companies in period 2009-2013. Logistic regression was implemented to 108 companies(i.e 540 firms-years). The findings of the research were family firms were more likely to appoint auditorwith industry expertise than non family firm, family firms that switched audit partners from non-specialiststo specialists had higher earning response coefficient (ERC) than nonfamily firms, positive association betweenfamily firms and industry specialist auditor selection came primarily from CEOs hired outside ratherthan family CEOs, among family firms, the likelihood of choosing industry specialist auditors increased withthe divergence between control rights and cash flow rights.